ChemInform Abstract: Rhodium‐Catalyzed Asymmetric Olefin Hydrogenation by Easily Accessible Aniline‐ and Pyridine‐Derived Chiral Phosphites. Issue 22 (13th May 2013) - Vallianatou, Kalliopi A.; Frank, Dominik J.; Antonopoulou, Georgia; Goergakopoulos, Spyros; Siapi, Eleni; Zervou, Maria; Kostas, Ioannis D.
Abstract (R)‐BINOL‐derived bidentate P, N‐phosphite ligands are prepared and tested in the hydrogenation of several prochiral olefins.